Obesity, Dietary Habits, and Body Image Perception in College Students at Sultan Ageng Tirtayasa University - Nufus Sulthonah; Syifa Marsyidah; Riska Kurnia; Widiya Putri; Qurratu A'yun; Nur Riva Angelina; Bella Apriliany; Raihan Fahrezi; Owen Hidayatullah (Journal of Health and Nutrition Research, 2023)
Central obesity is a condition of excess fat accumulation in the abdomen. Lifestyle factors such as consuming high-fat foods, low fiber intake, and low physical activity can contribute to central obesity. The objective of this study is to investigate the prevalence of obesity, dietary habits, and body image perception in college students at Sultan Ageng Tirtayasa University. This quantitative study was conducted using a cross-sectional design in the Nutrition Study Program, Faculty of Medicine, UNTIRTA, in November 2022.The population of the study was students of the Nutrition Study Program, batch 2020-2022, with a total of 121 students. A sample of 80 students was selected using a total sampling method. The results of the study showed that central obesity in college students was mostly caused by unhealthy lifestyle factors, such as not following a healthy lifestyle, unhealthy eating patterns, and low physical activity. Of the respondents, 67 (80.72%) did not follow a healthy lifestyle, while 13 (15.66%) followed a healthy lifestyle with a balanced diet. Most respondents (66.27%) had the habit of consuming fast food, with a frequency of consumption of 3 times per week in 24.1% of cases. The majority of respondents (63.86%) did not have the habit of exercising. These findings suggest that unhealthy lifestyle factors are major contributors to central obesity in college students of nutrition at Sultan Ageng Tirtayasa University.